Community-Based Digital Marketing Strategies in MSME Development: Contributions to the Creative Economy through Community Service - Frans Sudirjo; Kraugusteeliana Kraugusteeliana (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2026)
The development of digital technology has encouraged significant changes in marketing patterns within the Micro, Small, and Medium Enterprises (MSMEs) sector, particularly through the utilization of social media and digital communities as instruments for business development. This study aims to analyze community-based digital marketing strategies in MSME development and their contribution to the creative economy through community service activities. The study employed a literature review method using a qualitative approach and descriptive analysis. Data sources were obtained from Google Scholar, scientific journals, proceedings, and credible websites published between 2019 and 2026. The data collection process initially identified 50 articles, which were then screened based on thematic relevance, source quality, and alignment with the research focus, resulting in 28 main articles used in the study. The findings indicate that community-based digital marketing strategies are capable of increasing MSME competitiveness through market expansion, improved consumer engagement, strengthened local product branding, and enhanced social collaboration among business actors. Community service programs based on digital mentoring also contribute to improving digital literacy, marketing capabilities, and technological adaptation among MSME actors.